13, 13a-seco-protoberberines from the tubers of Corydalis yanhusuo and their anti-inflammatory activity. (February 2022) - Xia, Gui-Yang; Fang, Dong-Jie; Wang, Ling-Yan; Xia, Huan; Wang, Ya-Nan; Shang, Hong-Cai; Lin, Sheng
Abstract: Six undescribed protoberberine derivatives including two pairs of enantiomers, named yanhusanines G-L, along with fifteen reported protoberberine alkaloids, were isolated from the tubers of Corydalis yanhusuo . Among them, yanhusanines H-L feature a unique 13, 13a- seco skeleton which is rare in nature. Their structural elucidations were achieved by extensive spectroscopic analysis and quantum chemistry calculations. A biogenetic route for yanhusanines H-L was proposed. Bioassay results showed that yanhusanine J exhibited potent inhibitory effect against the nitric oxide (NO) production in lipopolysaccharide (LPS) induced RAW 264.7 cells (IC50  = 2.25 ± 1.32  μ M). Western blot analysis demonstrated that yanhusanine J exerted its anti-inflammatory effect via suppressing the nuclear factor kappa B (NF-κB) pathway, together with the decrease of the inflammatory factors TNF- α, IL-6 and IL-1 β . Furthermore, molecular simulation docking indicated that yanhusanine J had strong interaction with the active site of the inducible nitric oxide synthase (iNOS) protein. Graphical abstract: Six undescribed protoberberine derivatives including two pairs of enantiomers, named yanhusanines G-L were isolated from the tubers of Corydalis yanhusuo . Yanhusanine J exhibited potent anti-inflammatory effect. Image 1 Highlights: Five undescribed 13, 13a- seco -protoberberines were isolated from the tubers of Corydalis yanhusuo . Molecular docking revealed strong affinities of yanhusanine J with iNOS. Yanhusanine J exhibited potent anti-inflammatory effect by attenuating the NF-κB signaling pathway.